MANAGEMENT OF INNOVATIVE PROCESSES IN EDUCATIONAL INSTITUTIONS - Suyarova Surayyo (Bright Mind Publishing, 2025)
This article discusses the theoretical foundations and practical aspects of managing innovation processes in educational institutions. The author examines the essence of the concept of innovation, its life cycle, types and significance in the pedagogical system. Micro- and macro-level approaches to innovation processes, their internal logic and interaction with the environment are analyzed. Expanded and simple repetitive forms of innovations and factors affecting their success are also considered. The article also provides theoretical and practical recommendations necessary for effective management of innovative activities.
Keywords: innovation, innovative process, educational system, management, new idea, life cycle, pedagogical innovation, micro approach, macro approach, innovative activity.